PENERAPAN GOOD CORPORATE GOVERNANCE (GCG) PADA PT. PP LONDON SUMATRA INDONESIA TBK (BUKITHIJAU ESTATE) KABUPATEN MUSI RAWAS UTARA TAHUN 2016 - Dheo - Rimbano (JURNAL RISET TERAPAN AKUNTANSI, 2018)
This research was conducted at PT PP London Sumatera Indonesia Tbk (Bukit Hijau Estate) NorthMusi Rawas Regency with the purpose of research to know the application of the principles of Good Corporate Governance (GCG) at PT. PP London Sumatra Indonesia Tbk (Bukit Hijau Estate) North Musi Rawas Regency. Collecting technique is to conduct interviews with questionnaires distributed to33 respondents who are employees of PT PP London Sumatera Indonesia Tbk (Bukit Hijau Estate) North Musi Rawas Regency. Data analysis techniques used in this study using qualitative techniques. The results showed that the implementation of Good Corporate Governance (GCG) of PT PP London Sumatera Indonesia Tbk (Bukit Hijau Estate) North Musi Rawas Regency in accordance with the principles of Good Corporate Governance (GCG) that is Transparency, the calculation result shows84.24% that the achievement of transparency ( transparency) on Good Corporate Governance (GCG) at PT PP London Sumatera Indonesia Tbk (Bukit Hijau Estate) Musi Rawas Regency has been greatly realized. Accountability research results indicate 89.69% category is very materialized. Responsibility of research results of 85.45% in the highly realized category is the application of Good Corporate Governance (GCG). Independency value of achievement of 83.03%. Can be stated very realized. Fairness result of research is equal to 87.87% can be stated that in very materialized category.